PENDEKATAN STRATEGIS TERHADAP EVALUASI KARYAWAN UNTUK PENINGKATAN DAYA SAING PT SURYAGITA NUSANTARA CARGO EXPEDISI BANJARBARU - Damayanti, Adellia; Zakky Zamrudi; Syahrial Shaddiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the contribution of the current employee evaluation system and recommend a more strategic approach model to enhance the competitiveness of PT Suryagita Nusantara Cargo Expedisi Banjarbaru. Based on in-depth interview findings with the HR Manager, Operational Supervisor, and High-Performing Employees, the current evaluation system is concluded to be partial and tactical. While effective for administrative purposes and enforcing basic discipline, the system fails to measure strategic competencies (such as innovation and technology adaptation) and does not explicitly link individual performance to the company's long-term strategic goals. This gap creates structural demotivation among high-performing employees.The main recommendation proposed is a shift to an adjusted Objectives and Key Results (OKR) framework, complemented by the measurement of strategic behavioral competencies (Process Innovation and Cross-Functional Collaboration). This model is chosen for its transparent, forward-looking, and outcome-based nature, which directly promotes focus on ambitious and strategic results. Furthermore, it is suggested that evaluation be transformed from an annual process into a mechanism of real-time feedback and continuous coaching. Full integration of OKR results with talent management decisions (promotions and training) is key to making evaluation a strategic implementation instrument. By adopting this strategic approach, PT Suryagita Nusantara can transform its Human Resources from a controlled resource into the main driver of competitive advantage.